Measuring and Determinants of Inclusive Growth: Evidence from Indonesia - Dolly Mantora Hazmi; Syafruddin Karimi; Fajri Muharja (Universitas Ahmad Dahlan, 2022)
The understanding that high growth does not guarantee an increase in the welfare of society as a whole is the cause of the increasing popularity of the concept of inclusive growth. inclusive growth is found in Indonesia's National Medium-Term Development Plan (RPJMN) 2015-2019 and RPJMN 2020-2024. This indicates that the Indonesian government is very concerned with more equitable growth. But there is no measure that is able to describe inclusive growth. In empirical studies also still use a variety of measures. For that we try to promote one measure of inclusive growth with a pro-poor growth measure approach. Our measure has proven to be able to explain growth, poverty reduction and inequality better than other measures. We also analyze the determinants of inclusive growth using panel data. We place greater emphasis on the role of low-income communities in inclusive growth.